2015
DOI: 10.48550/arxiv.1509.05150
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Direct Urca processes involving singlet proton superfluidity in neutron star cooling

Abstract: A detailed description of the baryon direct Urca processes A: n → p + e + νe, B: Λ → p + e + νe, C: Ξ − → Λ + e + νe related to the neutron star cooling is given in the relativistic mean field approximation. The contributions of the reactions B and C on the neutrino luminosity are calculated by means of the relativistic expressions of the neutrino energy losses. Our results show that the total neutrino luminosities of the reactions A, B, C within the mass range 1.603-2.067M⊙ (1.515-1.840M⊙ for TM1 model) for G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…When the density is larger than 2-3 times the saturation density, hyperons appear in the neutron stars [6]. References [7][8][9][10][11] have studied the effects of hyperons on the N-DURCA process and suggested that the existence of hyperons can reduce the neutrino emissivity of the N-DURCA process. The hyperon direct URCA process also exists once the Λ hyperon appears [12].…”
Section: Introductionmentioning
confidence: 99%
“…When the density is larger than 2-3 times the saturation density, hyperons appear in the neutron stars [6]. References [7][8][9][10][11] have studied the effects of hyperons on the N-DURCA process and suggested that the existence of hyperons can reduce the neutrino emissivity of the N-DURCA process. The hyperon direct URCA process also exists once the Λ hyperon appears [12].…”
Section: Introductionmentioning
confidence: 99%